Opportunities and Threats of the Legally Facilitated Performance-Based Managed Entry Agreements in Slovakia: The Early-Adoption Perspective - Hospodková, Petra; Gilíková, Klára; Barták, Miroslav; Marušáková, Elena; Tichopád, Aleš (Healthcare, 2023)
Slovakia has adopted an amendment to Act No. 363/2011, regulating, among other things, drug reimbursement and is undergoing a significant change in the availability of innovative treatments for patients. High expectations are associated with arrangements related to performance-based managed entry agreements. Opinions and positions towards this change appear to be inconsistent, and for the further application of the law in practice and when setting up the main implementation processes, it is necessary to understand the positions and opinions of the individual actors who are involved in the PB-MEA process. The interviews were conducted in the period from 20 May to 15 August 2022 around the same time as the finalisation of the amendment to Act No. 363/2011 and its adoption. A roughly one-hour open interview was conducted on a sample of 12 stakeholders in the following groups: representatives of the Ministry of Health, health-care providers, pharmaceutical companies and others, including a health insurance company. The main objective was to qualitatively describe the perception of this topic by key stakeholders in Slovakia. The responses were analysed using MAXQDATA 2022 software to obtain codes associated with key expressions. We identified three main strong top categories of expressions that strongly dominated the pro-management interviews with stakeholders: legislation, opportunities and threats. Ambiguity and insufficient coverage of the new law, improved availability of medicinal products and threats associated with data, IT systems and potentially unfavourable new reimbursement schemes were identified as key topics of each of the said top categories, respectively. Among individual sets of respondents, there is frequent consensus on both opportunities and threats in the area of implementing process changes in PB-MEA. For the successful implementation of the law in practice, some basic threats need to be removed, among which in particular is insufficient data infrastructure.